Aristophanes and Politics : New Studies - Rosen, Ralph M.,; Foley, Helene P., (Columbia Studies in the Classical Tradition;, 2020)
The essays in this volume explore the many aspects of the "political" in the plays of Greek comic dramatist Aristophanes (5th century BCE), posing a variety of questions and approaching them through diverse methodological lenses. They demonstrate that "politics" as reflected in Aristophanes' plays remains a fertile, and even urgent, area of inquiry, as political developments in our own time distinctly color the ways in which we articulate questions about classical Athens. As this volume shows, the earlier scholarship on politics in (or "and") Aristophanes, which tended to focus on determining Aristophanes' "actual" political views, has by now given way to approaches far more sensitive to how comic literary texts work and more attentive to the complexities of Athenian political structures and social dynamics. All the studies in this volume grapple to varying degrees with such methodological tensions, and show, that the richer and more diverse our political readings of Aristophanes can become, the less stable and consistent, as befits a comic work, they appear to be.